Enhancing Teacher Creativity through Educational Game Tools at TK Negeri Pembina, Kediri: A Practical Approach - Wijaya, Intan Prastihastari (Dimar : Jurnal Pengabdian Masyarakat, 2024)
This service aims to empower kindergarten teachers in Semampir sub-district, Kediri City, by enhancing their creativity and proficiency in utilizing educational game tools. Recognizing the pivotal role of early childhood educators in shaping children's development, the initiative focuses on providing targeted training sessions at Pembina State Kindergarten. The training program encompasses theoretical teachings, interactive discussions, and practical exercises in designing and implementing educational games. By equipping teachers with these skills, the service endeavours to enrich their ability to create engaging and effective learning environments for young children. The training's impact has been positive, evident in the heightened creativity, enhanced knowledge, and improved resource utilization among participating teachers. These outcomes are crucial for advancing the quality of early childhood education, as they contribute to more stimulating and tailored educational experiences. Overall, this initiative underscores the importance of continuous professional development for kindergarten teachers, emphasizing innovation and resourcefulness in educational practices aimed at fostering holistic development in young learners.